Not All Beef Marketing Alliances Are the Same: A Review of Alliance Types - Thomas E. Anton (EDIS)
This is EDIS document FE362, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published November 2002.